Myopie nebo hypermetropie? - Pašová, P; Procházková, J; Cuvala, J (Ceska a slovenska oftalmologie, 2013)
INTRODUCTION: The study describes cases of patients screened for worse vision and headaches. We are trying to point out we can measure minus diopters even at latent hypemetropes. These patients come to a doctor for a variety of problems that may be caused by inadequate correction of ametropia. It is necessary to know about this possibility, and rather perform cycloplegia in sporadic cases. METHODS: Patients were measured at autorefractometer without mydriasis, and then after using UNITROPIC 1% or CYCLOGYL 1%. Both of these substances induce cycloplegia. Visual acuity with the best correction was tested with and without cycloplegia. RESULTS: After cycloplegia, a significant change in both objective and subjective refraction was detected in most of the selected patients. This change was within the meaning of a shift to hyperopia. Subsequent adjustment correction led to resolving of problems. CONCLUSION: The work should highlight the necessity of an individual approach of prescription of the best correction. Not always an autorefractometer gives correct information, the real-needed correction is completely different in some cases.
Keywords: hypermetropie; Young Adult; bolesti hlavy; zrakové testy; Male; zraková ostrost; Eyeglasses; Hyperopia; mladý dospělý; Vision Tests; Adult; dospělí; mužské pohlaví; myopie; Visual Acuity; Myopia; brýle; lidé; ženské pohlaví; Humans; Headache; Female